How clientelism varies: comparing patronage democracies. Issue 1 (2nd January 2020) - Berenschot, Ward; Aspinall, Edward
ABSTRACT: Clientelistic vote mobilization is a prominent electoral strategy in many of the world's democracies and electoral authoritarian regimes. Yet the comparative study of this practice, which involves exchanging personal favours for electoral support, remains strikingly underdeveloped. This special issue makes the case that clientelistic politics takes different forms in different countries, and that this variation matters for understanding democracy, elections, and governance. By comparing clientelistic vote mobilization in several countries – Mexico, Ghana, Sudan to Turkey, Indonesia, the Philippines, Caribbean and Pacific Islands states, and Malaysia – we unpack the concept of political clientelism and show that it is possible to identify different types of patronage democracies. In this introductory essay, we develop a comparative framework for this endeavour, showing that clientelism can be fruitfully compared in terms of the character of the networks that facilitate clientelistic exchange, the benefits that politicians offer in exchange for votes, and the degree to which politicians, and especially parties, control the distribution of state resources. These comparisons lead to the identification of different types of patronage democracies, notably community-centred and party-centred varieties. Building on this framework, this special issue shows that the comparative study of clientelistic politics offers analytical promise for scholars of democracy and democratization.